Penerapan Model Pembelajaran Project Based Learning dengan Pendekatan Demonstrasi Materi Energi Mekanik - Rambing, Sheny Natasya; Makahinda, Tineke; Mandolang, Aswin Hermanus (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2022)
The purpose of this study is to improve learners' learning outcomes by using Project-Based Learning (PjBL) models with a demonstration approach to mechanical energy materials. The method used in this study was an experiment with the design of one group pretest posttest desaign. The research sample amounted to 25 learners. Data analysis in this study using SPSS 22 From the results of the data analysis obtained an average pretest score of 54.75 and a posttest value of 79.17 the results of the hypothesis test showed that there was an increase in learner learning outcomes using the project-based learning model with a demonstration approach. Thus it can be concluded that the average score of the learning outcomes of learners who are given treatment by using the application of project-based learning models with a demonstration approach is higher than the average physics learning outcome when not given treatment.